Perlindungan Hak Perempuan Dalam Fatwa MUI Bidang Munâkaḥat Perspektif Maşlaḥah - Alwi, Mujahid; R, Rahmatullah; Maloko, H.M. Thahir (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to discuss the protection of women's rights in the MUI Fatwa in the field of Munâkaḥat from a Maşlaḥah perspective. This research is qualitative research with the type of library research. The data collection method used in this research is literature study. The research results show that there is Maşlaḥah obtained regarding the protection of women's rights in the MUI fatwa in the field of Munâkaḥat. The MUI or Indonesian Ulema Council, the main Islamic administrative body in Indonesia, considers such relations to be legally dangerous because they are considered to violate public regulations. The MUI generally underlines the importance of complying with Islamic norms and state regulations, which is legally dangerous because it is considered to violate public regulations requiring official registration.